Transient Analysis of a Coolant-to-Refrigerant Heat Exchanger to Provide Temporary High Performance in an Automotive Vehicle - (:unkn) unknown (My University, 2018)
The objective of this thesis is to provide a numerical and experimental design tool to understand the heat transfer analysis of a coolant reservoir being chilled at a sub-ambient temperature with a goal of eventually providing a transient burst in performance. A high performance vehicle usually has a liquid charge air cooler that cools air before entering the engine. This liquid charge air cooler cools the air by using a specific coolant coming from the low temperature radiator. This study involves a coolant reservoir independent of the low-temperature radiator to provide coolant at a sub-ambient temperature to the liquid charge air cooler on a non-on-going basis. This causes the air in the liquid charge air cooler to be colder than usual, which provides a better volumetric efficiency that results in a higher performance in the engine. The coolant in the reservoir heat exchanger that is being cooled by the refrigerant coming from the air conditioning unit in a vehicle is stagnant. Since this study is analyzing the coolant behavior and temperature, this thesis provides a comprehensive investigation on the natural convective heat transfer processes due to the motionless coolant being cooled. A thermodynamic analysis coupled with a thermal resistance calculation provides a custom lumped capacitance model equation to show a relationship between the time and coolant temperature. Results from this analytical calculation and experimental simulations using computational fluid dynamics software (Star CCM+) delivers a detailed understanding of the difference from cooling the coolant from the top compared to cooling the coolant from the bottom while understanding the importance of surface area for improved heat transfer.
Keywords: Heat Exchanger; Heat Transfer; Natural Convection